Titus Groan - Peake, Mervyn, 1911-1968 (The Overlook Press, an imprint of ABRAMS, 2021)
"As the novel opens, Titus, heir to Lord Sepulchrave, has just been born. He stands to inherit the miles of rambling stone and mortar that form Gormenghast Castle. Inside, all events are predetermined by a complex ritual whose origins are lost in history and the castle is peopled by dark characters in half-lit corridors. Dreamlike and macabre, Peake s extraordinary novel is one of the most astonishing and fantastic works in modern English fiction."--